2007
DOI: 10.1111/j.1442-200x.2007.02432.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of childhood epilepsy in Vietnam: cases in Bach Mai Hospital

Abstract: Concerning the causes, the following were noted: (i) the rate of infectious diseases and trauma as causes of epilepsy was considerably higher in Vietnam than in developed countries; (ii) certain infectious diseases could be prevented if vaccinations and public health knowledge were improved; and (iii) the number of trauma cases, mainly due to traffic accidents, would likely be reduced if the traffic system was improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Some children with CNS abnormalities die after birth ( 10 ), and those who survive may suffer from psychomotor developmental abnormalities. A study by Shirasaka et al, examining the causes of epilepsy in children treated at Bach Mai Hospital from 2002 to 2004, reported that congenital CNS abnormalities accounted for 12% of cases ( 11 ). The early and accurate detection of CNS abnormalities can provide clinicians with the necessary information to make a prognosis, perform prenatal counseling, and determine the most appropriate treatment after birth.…”
Section: Introductionmentioning
confidence: 99%
“…Some children with CNS abnormalities die after birth ( 10 ), and those who survive may suffer from psychomotor developmental abnormalities. A study by Shirasaka et al, examining the causes of epilepsy in children treated at Bach Mai Hospital from 2002 to 2004, reported that congenital CNS abnormalities accounted for 12% of cases ( 11 ). The early and accurate detection of CNS abnormalities can provide clinicians with the necessary information to make a prognosis, perform prenatal counseling, and determine the most appropriate treatment after birth.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we assume that SCARs caused by CBZ and allopurinol in Vietnam might then be largely preventable, especially as genetic screening programs would likely be beneficial in view of the high prevalence of HLA-B*15:02 and HLA-B*58:01, similar to that in the Taiwanese and Thai populations 33, 34. Moreover, as Vietnam is a typical developing country with a high burden of disease requiring treatment with CBZ or allopurinol (epilepsy, mental disorders, pain syndromes and hyperuricemia),35, 36, 37, 38, 39 alternative medications to CBZ or allopurinol may be too costly. Taking epilepsy as an example, the treatment gap in Vietnam (defined as the proportion of patients who are not given appropriate treatment for active epilepsy) was reported at 84.7% (compared with 56% in other countries) 82 .…”
Section: Introductionmentioning
confidence: 99%